The RNA polymerase II CTD "orphan" residues: Emerging insights into the functions of Tyr-1, Thr-4, and Ser-7. Issue 1 (1st January 2018) - Yurko, Nathan M.; Manley, James L.
ABSTRACT: The C-terminal domain (CTD) of the RNA polymerase II largest subunit consists of a unique repeated heptad sequence of the consensus Tyr1–Ser2–Pro3–Thr4–Ser5–Pro6–Ser7. An important function of the CTD is to couple transcription with RNA processing reactions that occur during the initiation, elongation, and termination phases of transcription. During this transcription cycle, the CTD is subject to extensive modification, primarily phosphorylation, on its non-proline residues. Reversible phosphorylation of Ser2 and Ser5 is well known to play important and general functions during transcription in all eukaryotes. More recent studies have enhanced our understanding of Tyr1, Thr4, and Ser7, and what have been previously characterized as unknown or specialized functions for these residues has changed to a more fine-detailed map of transcriptional regulation that highlights similarities as well as significant differences between organisms. Here, we review recent findings on the function and modification of these three residues, which further illustrate the importance of the CTD in precisely modulating gene expression.